2020
DOI: 10.1158/1541-7786.mcr-19-0934
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive CHK1 Expression Drives a pSTAT3–CIP2A Circuit that Promotes Glioblastoma Cell Survival and Growth

Abstract: High-constitutive activity of the DNA damage response protein checkpoint kinase 1 (CHK1) has been shown in glioblastoma (GBM) cell lines and in tissue sections. However, whether constitutive activation and overexpression of CHK1 in GBM plays a functional role in tumorigenesis or has prognostic significance is not known. We interrogated multiple glioma patient cohorts for expression levels of CHK1 and the oncogene cancerous inhibitor of protein phosphatase 2A (CIP2A), a known target of high-CHK1 activity, and e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The impact of CHK1 inhibition on GB cells was also studied using SB18078 and PF477736, confirming an influence on colony and tumor sphere formation, as well as cell proliferation. Khanna et al also confirmed that CHK1 acts via protein phosphatase 2A in promoting GB cell growth [ 183 ]. Unfortunately, in AST, a phase I study on PF477736 combined with gemcitabine was terminated due to business reasons (NCT00437203) [ 29 ].…”
Section: Ddr (Radio)pharmaceuticalsmentioning
confidence: 98%
“…The impact of CHK1 inhibition on GB cells was also studied using SB18078 and PF477736, confirming an influence on colony and tumor sphere formation, as well as cell proliferation. Khanna et al also confirmed that CHK1 acts via protein phosphatase 2A in promoting GB cell growth [ 183 ]. Unfortunately, in AST, a phase I study on PF477736 combined with gemcitabine was terminated due to business reasons (NCT00437203) [ 29 ].…”
Section: Ddr (Radio)pharmaceuticalsmentioning
confidence: 98%
“…Similarly, Khanna et al, in their study, showed a decrease in expression for all PP2A subunits in glioma tissues compared to healthy tissues, further strengthening the evidence of the oncogenic role of CIP2A in gliomas. Depletion of CIP2A expression in GBM cells induces senescence and prevents tumor growth in vitro and in vivo [ 60 ]. Gao et al demonstrated that knockdown of CIP2A in GBM cell lines LN229 and A172 led to an inhibition of cell activity and cell cycle arrest [ 43 ].…”
Section: Role Of Cip2a In Glioma and Gbmmentioning
confidence: 99%
“…Instead, its expression is enhanced due to constitutive DDR activity 42,51 , TP53 inactivation 20 , and EGFR pathway activation 21 , which are all molecular hallmarks of BLBC 1, 3 . Our data expand on these findings by demonstrating induction of Cip2a mRNA expression in premalignant mammary tissue of DMBA-treated mice ( Fig.…”
Section: Clinical and Functional Relevance For Cip2a In Human Blbcmentioning
confidence: 99%